The Strategy of Islamic Boarding School in Promoting Moral Education Based on Local Wisdom - Nurlaela, Nurlaela; Zaki, M.; Wildan, Wildan; Mukhlis, Mukhlis; Fattah, Abdul; Hadisaputra, Prosmala (PAEDAGOGIA, 2024)
This current study delves into the strategies employed by Islamic boarding schools (Pesantren) in promoting character education grounded in local wisdom. The investigation is guided by a central research question: "How do Islamic boarding schools strategize to promote morality education grounded in local wisdom? Utilizing a qualitative approach, the research design adopted for this study is a case study, conducted at Selaparang Islamic boarding school in West Lombok. Data collection methods encompassed interviews, observations, and document analysis. The analytical procedure employed is the interactive analysis procedure recommended by Miles, Huberman, and Saldana, comprising data collection, data condensation, data presentation, and drawing conclusions. The study reveals that the promotional strategies employed by Islamic boarding schools in advancing character education based on local wisdom include: first, aligning the vision and mission of the boarding school with local wisdom; second, leveraging social media platforms, specifically Instagram and YouTube channels. The findings of this study contribute to a comprehensive understanding of the promotional strategies implemented by Islamic boarding schools. Furthermore, the study recommends the development of character education promotion strategies grounded in local wisdom through the effective utilization of social media